Multiple tectonomagmatic reactivation of the unexposed basement in the northern Siberian craton: from Paleoproterozoic orogeny to Phanerozoic kimberlite magmatism. Issue 8 (28th April 2022) - Skuzovatov, Sergei Yu.; Shatsky, Vladislav S.; Wang, Qin; Ragozin, Alexey L.; Kostrovitsky, Sergey I.
ABSTRACT: Zircon xenocrysts from two diamond-barren kimberlite pipes (Leningrad and Ruslovaya) in the West Ukukit kimberlite field opened a 'window' to the buried crustal basement in the northern Siberian craton. Zircon U-Pb ages reveal a close affinity of the basement of the Khapchan belt to the Archaean Anabar province and a significant tectonomagmatic reworking in the Paleoproterozoic ( 2.1–1.8 Ga) due to collision between the Anabar province and the Olenek province. The West Ukukit kimberlite field experienced multiple tectonomagmatic reactivation from 670 to 144 Ma, which can be attributed to interaction of the deep crust with mantle-derived melts. Hf isotope composition of zircon xenocrysts reveals significant addition of juvenile material into the crust during the Paleoproterozoic orogeny in diamond-barren kimberlite fields, which is different from the reworking crust in the southern Yakutia diamondiferous kimberlite fields. Eruption of the Leningrad and Ruslovaya pipes were constrained as the Late Jurassic, much later than the well-known Late Silurian-Earth Devonian kimberlites in the West Ukukit kimberlite field. A NE-trending, >2000 km long kimberlite corridor is proposed to account for a prolonged lithospheric channel for episodic eruption of kimberlites in the Siberian craton. The diamond storage in the lithosphere beneath the West Ukukit kimberlite field may have been largely reduced by the Paleoproterozoic orogeny and Phanerozoic reworking.